Comparison of 1064-nm Nd:YAG picosecond laser using fractional micro-lens array vs. ablative fractional 2940-nm Er:YAG laser for the treatment of atrophic acne scar in Asians: a 20-week prospective, randomized, split-face, controlled pilot study - Dai, Ru; Cao, Yiyu; Su, Yiping; Cai, Suiqing (Frontiers in Medicine, 2023)
The 1064-nm Nd:YAG picosecond lasers using fractional micro-lens array (P-MLA) was a promising therapy for skin resurfacing. However, no studies have compared P-MLA with ablative fractional 2940-nm Er:YAG lasers (AF-Er) in the treatment of atrophic acne scars.To evaluate the efficacy and safety of P-MLA and AF-Er for the treatment of atrophic acne scars.We performed a prospective, randomized, split-face, controlled pilot study. Thirty-one Asian patients with mild to moderate atrophic acne scars underwent four consecutive sessions of randomized split-face treatment with P-MLA and AF-Fr at 4-week intervals. The efficacy of the two devices were evaluated by Echelle d'Evaluation Clinique des Cicatrices d'acne (ECCA) grading scale, Investigator's Global Assessment (IGA) score and patient's satisfaction. VISIA analysis was also performed to evaluate the pore and skin texture. Adverse events were recorded at each follow-up.The P-MLA afforded comparable clinical responses in scar appearance as AF-Er based on the investigator's assessments (ECCA percent reduction: 39.11% vs. 43.73%; IGA score: 2.97 ± 0.65 vs. 3.16 ± 0.68; P＞0.05 for both). However, the result of patient satisfaction indicated the AF-Ertreated side achieved a slightly greater improvement in scar appearance (3.97 ± 0.78 vs 3.55 ± 0.71; 2 This is a provisional file, not the final typeset article P＜0.05). Overall, the two devices did not differ largely in terms of efficacy. VISIA analysis revealed similar changing patterns of the pore and skin texture between two devices. For safety profiles, no serious side effects were reported on both sides. The P-MLA showed lower pain level, shortened duration of crust shed and edema, and less occurrence of PIH (P＜0.05 for all).Compared with AF-Er, P-MLA afforded comparable effect and more safety profiles in treating atrophic acne scars in Asian patients.